Legal effect of the ECtHR’s judgments in the legal system of Russian Federation - Biryukov, P. N.; Бирюков, П. Н.; Бірюков, П. М. (Одеса : Фенікс, 2013)
The article deals with fundamental questions of European Court of human Rights judgments arrangement in the Russian legal system. Particular attention is paid to the implementation of European Court of human Rights judgments by Russian courts, both common and commercial.

В статье рассмотрены концептуальные вопросы места и роли постановлений еспч в правовой системе Российской Федерации. особое внимание уделено применению решений еспч российскими судами: как арбитражными, так и общей юрисдикции.

У статті розглянуті концептуальні питання місця і ролі рішень ЄСПЛ у правовій системі Російської Федерації. Особливу увагу приділено застосуванню рішень ЄСПЛ російськими судами: як арбітражними, так і загальної юрисдикції.
Biryukov P. N. Legal effect of the ECtHR’s judgments in the legal system of Russian Federation / P. N. Biryukov // Правове забезпечення ефективного виконання рішень і застосування практики Європейського суду з прав людини : матер. 2-ї Міжнар. наук.-практ. конф. (Одеса, 20-21 вересня 2013 р.) / за ред. С. В. Ківалова ; НУ «ОЮА». – Одеса : Фенікс, 2013. – С. 268-277.
Keywords: European Court of Human Rights; legal system of Russian Federation; human rights; sources of law; Европейский суд по правам человека; правовая система Российской Федерации; права человека; источники права; Європейський суд з прав людини; правова система Російської Федерації; права людини; джерела права